METHOD OF THE VIBRATING DIAGNOSTICS OF DEFFECTS OF ELASTIC DESIGNS ON THE BASIS OF THE ANALYSIS OWN FORMS OF FLUCTUATIONS - A. V. Kositsyn (Приборы и методы измерений, 2015)
Work is devoted analytical methods of the vibrating diagnostics arising defects in the environment of ANSYS. The criterion of an estimation of a technical condition of elastic designs is offered. As a diagnostic sign of detection of defects in a material of an elastic body it is offered to use own forms of fluctuations with various parameters of supervision. For check of efficiency of the given way numerical experiment on an example of a flat plate is made.